Photocatalytic Dynamic Membrane Containing Graphitic Carbon Nitride/Zirconium dioxide Nanocomposite for MB and CR Dye Removal under Household LED Lamp - Marjan Tanzifi; Mohsen Jahanshahi; Majid Peyravi; Soodabeh Khalili (Journal of Water and Environmental Nanotechnology)
Dye-containing wastewater is a major pollutant that can irreversibly damage the environment. Ultrafiltration membrane technology combined with photocatalysis is used for treatment of dye-containing solutions. To remove dye pollution, Methylene blue (MB) and Congo red (CR), graphitic carbon nitride (CNG) and its zirconium dioxide nanocomposite (CNGZ) were used in the photocatalytic dynamic membrane system in both self-forming and pre-coated modes under household LED light. The filtration results of the self-forming membrane showed that the pure CNG- and nanocomposite-based photocatalytic membrane systems were more efficient for MB and CR dyes removal than the photocatalytic system in batch mode. In addition to improving dye molecule removal efficiency, adding the photocatalyst to the PES membrane also significantly increased water flux. Moreover, the respective MB and CR rejection rates were 29% and 47% for the pure PES membrane and 89% in 120 min and 100% in 80 min for the CNGZ-based photocatalytic membrane. This suggests that the photocatalytic membrane system is a more effective dye pollution remover than the pure PES. For comparison, the pre-coated dynamic membrane system used for MB dye removal was good for removing 98.6% within 20 min. The results suggest that CNGZ-based photocatalytic dynamic membrane is a promising technology for increasing dye molecules removal efficiency and flux in remediation of dye-containing wastewater.